Upgrade of the resonance ionization laser ion source at ISOLDE on-line isotope separation facility: new lasers and new ion beams - Fedosseev, Valentin N.; Fink, Daniel (Review of scientific instruments, 2012)
The resonance ionization laser ion source (RILIS) produces beams for the majority of experiments at the ISOLDE on-line isotope separator. A substantial improvement in RILIS performance has been achieved through a series of upgrade steps: replacement of the copper vapor lasers by a Nd:YAG laser; replacement of the old homemade dye lasers by new commercial dye lasers; installation of a complementary Ti:Sapphire laser system. The combined dye and Ti:Sapphire laser system with harmonics is capable of generating beams at any wavelength in the range of 210-950 nm. In total, isotopes of 31 different elements have been selectively laser-ionized and separated at ISOLDE, including recently developed beams of samarium, praseodymium, polonium, and astatine.
Gesehen am 14.11.2018